Delayed Presentation of Porta Hepatis Injury Following Blunt Abdominal Trauma. Issue 4 (1997) - Lau, L. L.; Diamond, T.
Abstract : A 73 year old lady developed abdominal pain, anaemia and obstructive jaundice 18 days after a road traffic accident. The jaundice was due to compression of the biliary confluence by a haematoma which was caused by a laceration of the left portal vein. The portal vein was repaired (lateral venorrhaphy) and post-operative recovery was uncomplicated. Porta hepatis injuries are difficult to diagnose and delayed presentation is not uncommon. Significant morbidity and mortality may ensue if aggressive management is not adopted.